2021
DOI: 10.1177/02646196211047731
|View full text |Cite
|
Sign up to set email alerts
|

Facebook experiences of visually impaired students: A deconstruction of the challenges and benefits

Abstract: This study explores the motivation for usage, benefits, and strategies to overcoming the challenges visually impaired people face in their Facebook interactions. Using in-depth interviews and a narrative analysis of five visually impaired students at the University of Cape Coast, we found that Facebook usage among visually impaired students, although unique in experiences and gratifications, has promoted the formation and strengthening of their social bonds in the community of visually impaired people and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Furthermore, perceived social support has been connected to quality of life through a negative correlation with depression (Gençöz & Özlale, 2004). It is possible that since online communication fosters weak-tie connections (Ellison & boyd, 2013;Ellison et al, 2007;Quainoo et al, 2021), communication on Facebook does not foster trust which would make users feel that social support would be available if needed. Conversely, research on sighted individuals showed that communication on social networking sites had a long-term positive effect on life satisfaction (Dienlin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, perceived social support has been connected to quality of life through a negative correlation with depression (Gençöz & Özlale, 2004). It is possible that since online communication fosters weak-tie connections (Ellison & boyd, 2013;Ellison et al, 2007;Quainoo et al, 2021), communication on Facebook does not foster trust which would make users feel that social support would be available if needed. Conversely, research on sighted individuals showed that communication on social networking sites had a long-term positive effect on life satisfaction (Dienlin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered one of the most accessible social network sites by users with disability and has offered them a degree of access that was not possible in other social network sites before (Asuncion et al, 2012;Quainoo et al, 2021). However, it is worth noting that individuals with congenital visual impairment have been more satisfied with Facebook compared to individuals with adventitious impairment (Quainoo et al, 2021). Even though Facebook still presents accessibility challenges to individuals with visual impairment (Babu, 2014; S. M. Lee et al, 2014;Nobre et al, 2018;Quainoo et al, 2021), the cooperation between its creators and the American Foundation of the Blind (Enajeh et al, 2018) showed its commitment to ameliorate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations